Development and Psychometric Evaluation of Alternate Short Forms of the Action Naming Test. (5th April 2021) - Pinto-Grau, Marta; O'Connor, Sarah; Murphy, Lisa; Heverin, Mark; Vajda, Alice; Hardiman, Orla; Pender, Niall
Abstract: Objective: The action naming test (ANT) is a confrontation naming task used to assess the ability to name action words. This study aimed to create two short forms of the ANT and assess their equivalence, reliability, and comparability to the long form. Methods: In total, 100 healthy adults (31 females and 69 males), aged 34–89 years ( M = 64 and SD = 10.4) were recruited. Short forms were developed using a split-half procedure. Results: No significant differences were observed between short forms on mean performance and distribution of scores for correct spontaneous responses, responses after semantic cue and total correct responses after cueing, but a higher number of accurate responses were prompted after phonemic cueing for Form A. Significant strong correlations between short forms and with the full form were encountered, although a weak correlation was found between short forms on performance after semantic cueing. IQ and age were significant predictors of action word retrieval. Whereas IQ also predicted post-cueing performance in all ANT forms, age predicted performance only for Form B. Conclusion: The two ANT short forms are equivalent when considering total spontaneous responses and total correct responses after cueing, but semantic and phonemic cues evoked different responses on the two forms. The two short forms were also affected differently by demographics. When the psychometric equivalence of Forms A and B was examined, the strict conditions for parallel forms were not met for all performance indices. Therefore, these newly developed short versions should be considered as alternate forms.